Agile Leadership, Digital Transformation, And Employee Performance: The Role Of Work Engagement - Tiong, Piter; Adi, Yusram; Irwan, Andi (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study examines how agile leadership and digital transformation influence employee performance, with work engagement as a mediating variable. Novelty – The research develops an integrated model linking leadership agility, digital transformation, and engagement in small service enterprises, extending prior studies that focus on large corporations or isolate these constructs. Method – Data were collected from 42 employees of Café Grind & Full in Makassar using a saturated sampling approach. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied for analysis. Findings – Agile leadership significantly strengthens digital transformation and engagement, while digital transformation improves both engagement and performance. Work engagement emerged as the strongest predictor and mediating mechanism. Theoretical and Practical Implications – Theoretically, the study advances understanding of engagement as a psychological bridge connecting leadership and technology to performance. Practically, it highlights the importance for managers to cultivate agile leadership, adopt user-friendly digital systems, and reinforce engagement strategies to optimize outcomes in small service firms.